2006
DOI: 10.1007/s00299-005-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and reproducible Agrobacterium-mediated transformation of sorghum

Abstract: A rapid and reproducible Agrobacterium-mediated transformation protocol for sorghum has been developed. The protocol uses the nptII selectable marker gene with either of the aminoglycosides geneticin or paromomycin. A screen of various A. tumefaciens strains revealed that a novel C58 nopaline chromosomal background carrying the chrysanthopine disarmed Ti plasmid pTiKPSF(2), designated NTL(4)/Chry5, was most efficient for gene transfer to sorghum immature embryos. A NTL(4)/Chry5 transconjugant harboring the pPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 27 publications
1
104
0
2
Order By: Relevance
“…Potential impact of biotechnology for improving composition and plant properties of herbaceous feedstocks is in its infancy [43,53,90,92,93,110], but represents an exciting area of research. The development of genetically engineered plants with improved feedstock properties could fast-track bioenergy exploitation; although widespread acceptance of these engineered plants are likely to face public opposition, especially for native prairie species such as switchgrass.…”
Section: Discussionmentioning
confidence: 99%
“…Potential impact of biotechnology for improving composition and plant properties of herbaceous feedstocks is in its infancy [43,53,90,92,93,110], but represents an exciting area of research. The development of genetically engineered plants with improved feedstock properties could fast-track bioenergy exploitation; although widespread acceptance of these engineered plants are likely to face public opposition, especially for native prairie species such as switchgrass.…”
Section: Discussionmentioning
confidence: 99%
“…They include cat, npt II, hpt, bar and manA. Neomycin phosphotransferase II (npt II) gene isolated from E.coli conferring resistance to the antibiotic Kanamycin is one of the commonly used selection strategy for sorghum (Howe et al, 2006;Tadesse and Jacobs, 2004;Battraw and Hall, 1991). Hagio et al, (1991) reported the use of Hygromycin B phosphotransferase (hpt) as well as Neomycin phosphotransferase II (nptII) genes to confer Hygromycin and Kanamycin resistance, respectively.…”
Section: Role Of Selectable Markersmentioning
confidence: 99%
“…Further screening was conducted through PCR analysis, the transformation frequency was calculated and found to be within the cited range (Emani et al, 2002;Gao et al, 2005b;Zhao et al, 2000;Howe et al, 2006) from 0.2 to 4.5%, even though these reports were on highly regenerable and transformable genotypes, e.g. P898012 and TX430.…”
Section: Analysis Of the Transgenic Plantsmentioning
confidence: 99%